Development of public and private sector partnership: managerial aspects - Živilė Tunčikienė; Adriana Grenčiková; Ilona Skačkauskienė (Business: Theory and Practice, 2014)
A partnership between different sectors fundamentally becomes an essential strategic tool in pursuit of the growth in the quality of social life and thus a sustainable development of a state. The value created by collaborate activities of companies and institutions, while increasing the capacity to fulfil social needs, depends on managerial abilities of institutions. Subsequent to analysis of both theoretical and practical aspects of public–private partnership and its management, the research aims to present milestones pertaining to the development of the latter. The tasks for achieving goals are as follow: the analysis of the concept of public–private partnership, the examination of the partnership principles and forms, the analysis of management models, the study of legal and administrative partnership aspects, the evaluation of key partnership problems and the search of their solutions.